Pengembangan Strategi Pemasaran Produk Unggulan Desa Laweyan Melalui Kegiatan Branding UMKM Dodol Pisang - Erika Anjani Widianti; Aufa Izzudin Baihaqi (Yayasan Daarul Huda Kruengmane, 2023)
Indonesia is a country that has various kinds of wealth, not only from nature but also from processed foods and crafts. Indonesian specialties, especially in food and beverage products, are well managed by industries in Indonesia. Not only the Indonesian industry, UMKM’s also take part in producing processed food and specialty drinks with their innovations and creations. One of them is through the existence of business development activities from banana ingredients, which is one of the efforts to increase the selling value of local products which will have a direct impact on the income of local UMKM’s. One of the UMKM’s where KKNT-MBKM students serve, namely in Probolinggo City, has problems in product development and marketing factors. Therefore, the purpose of this service activity is to plan marketing strategies for these UMKM’s to launch their business activities. The method used is qualitative with the type of data collection through observation, interviews and documentation of activities for UMKM person. The results this service activity for UMKM products have developed and the marketing aspects are going well.